Legal Loopholes in the Regulation of Corruption Eradication in the Management of State-Owned Enterprise Investment Funds in the Tourism Sector - Ikrom, Yaumil; Agustin, Eka Wulandari; Tamara, Eriska; Saliman, Abdul Rasyid; Agustina, Enny (Dinasti Research, 2024)
This study examines the legal gap in the regulation of corruption eradication in the management of State-Owned Enterprises (SOEs) investment funds in the tourism sector. SOEs have a strategic role in developing national tourism through the management of large-scale assets and investments sourced from separate state assets. However, despite the existence of legal frameworks such as Law No. 19 of 2003 concerning SOEs, Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, Law No. 25 of 2007 concerning Investment, and Law No. 10 of 2009 in conjunction with Law No. 6 of 2023 concerning Tourism, there are no specific regulations regarding the prevention, supervision, and action against corruption in SOEs' tourism investments. This legal gap has resulted in overlapping authority between supervisory institutions, weak transparency in financial reports, and the absence of clear indicators to classify acts as criminal acts of corruption in this sector. This study uses a normative juridical method with a statutory and conceptual approach to analyze regulatory gaps, examine international practices such as the provisions of the United Nations Convention against Corruption (UNCAC), and formulate the need for reformulation of specific regulations. The analysis demonstrates the urgency of establishing detailed regulations that address integrated oversight mechanisms, technology-based transparency, proportionate criminal and administrative sanctions, and integrate the role of supervisory institutions to prevent and prosecute corruption from the planning stage through project evaluation. Implementation of these specific regulations is expected to increase legal certainty, investor confidence, and the sustainability of national tourism development.